Case report: A complex case of valve-in-valve TAVI and left bundle branch pacing for severe aortic regurgitation with partially corrected type A aortic dissection and low ejection fraction - Mihailovič, Peter Marko; Žižek, David; Vitez, Luka; Holc, Primoz; Klokočovnik, Tomislav; Bunc, Matjaž (Frontiers in Cardiovascular Medicine, 2023)
Background: Aortic regurgitation is a major concern following transcatheter aortic valve implantation (TAVI) as even low-grade regurgitation is associated with increased mortality. This is of particular concern in patients with preexisting aortic disease with increased risk of TAVI valve slippage. Furthermore, conduction system disturbances after TAVI, namely left bundle branch block (LBBB), could have an additional detrimental effect on cardiac function. Case presentation: The report documents a succesful treatment strategy of a frail patient with a bicuspid aortic valve and aortic disease after valve-sparing surgical repair in 1998, who subsequently developed aortic stenosis and underwent TAVI with a Evolut R self-expanding aortic valve. Progression of the aortic disease and dilatation of the aortic root as well as leaflet degeneration over the following years caused aortic regurgitation of the self-expanding aortic valve resulting in left ventricular dilatation and heart failure along with LBBB and mechanical dyssynchrony of the left ventricle (LV). Diagnostic workup of the patient showed persistence of the aneurysm distal to the graft with a dissection spanning the ascending aorta, arch and terminating proximal to the aortic isthmus. After heart team consideration, a balloon-expandable valve was chosen for a valve in valve (ViV) procedure to provide sufficient radial force for the expansion of the preexisting valve and correct the regurgitation. Due to the anatomy, a J wire and pigtail catheter were used successfully for safe approach and successful placement of the valve. Following the procedure intermittent complete atrioventricular block was observed in addition to the preexisting left bundle branch block necessitating resynchronization pacing. Due to anatomical considerations, ease of placement and good expected level of resynchronization due to proximal block, we opted for left bundle branch pacing which showed improvement in dyssynchrony of the left ventricle and improvement in LV function at follow-up. Conclusion: Valve in valve implantation of a balloon expandable Myval TAVI device to treat aortic regurgitation caused by valve slippage of a self-expanding valve is feasible in complex anatomical scenarios. Left bundle branch pacing is a viable alternative for correction of mechanical dyssynchrony in complex patients with LBBB and anatomical challenges necessitating resynchronization.